2012
DOI: 10.1002/adfm.201200063
|View full text |Cite
|
Sign up to set email alerts
|

A Spider's Fang: How to Design an Injection Needle Using Chitin‐Based Composite Material

Abstract: Spiders mainly feed on insects. This means that their fangs, which are used to inject venom into the prey, have to puncture the insect cuticle that is essentially made of the same material, a chitin‐protein composite, as the fangs themselves. Here a series of structural modifications in the fangs of the wandering spider Cupiennius salei are reported, including texture variation in chitin orientation and arrangement, gradients in protein composition, and selective incorporation of metal ions (Zn and Ca) and hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
166
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(181 citation statements)
references
References 44 publications
6
166
1
8
Order By: Relevance
“…Billfish rostra are subject to periodic loadings over long periods of time, which may result in fatigue damage and favor the formation of microcracks in this stiffer area, as in bone and nacre (Currey, 1984). Similar gradients of stiffness have been reported in other biological structures including bird feathers (Macleod, 1980;Bonser and Purslow, 1995), squid beaks (Miserez et al, 2008) and spider fangs (Politi et al, 2012); the latter two systems also acting as predatory weapons, similar to billfish rostra. In addition, the higher incidence of remodeled bone morphology in the distal region of the rostrum suggest that the tissue is under regular loading and therefore more prone to damage and consequently, remodeling (Atkins et al, 2014).…”
Section: Discussionmentioning
confidence: 62%
“…Billfish rostra are subject to periodic loadings over long periods of time, which may result in fatigue damage and favor the formation of microcracks in this stiffer area, as in bone and nacre (Currey, 1984). Similar gradients of stiffness have been reported in other biological structures including bird feathers (Macleod, 1980;Bonser and Purslow, 1995), squid beaks (Miserez et al, 2008) and spider fangs (Politi et al, 2012); the latter two systems also acting as predatory weapons, similar to billfish rostra. In addition, the higher incidence of remodeled bone morphology in the distal region of the rostrum suggest that the tissue is under regular loading and therefore more prone to damage and consequently, remodeling (Atkins et al, 2014).…”
Section: Discussionmentioning
confidence: 62%
“…Measurements of the mechanical properties after removing metals from the cuticle showed 2-fold decrease in the hardness, suggesting a significant impact of the coordination complex on the material properties3. In the fangs of the wandering spider Cupiennius salei , Zn-His coordination complexes were also found in the matrix of chitin and Zn-containing proteins2. Connection was then identified between the mechanical properties and Zn/Cl enrichment in this fiber-reinforced biocomposite.…”
mentioning
confidence: 87%
“…Many biological materials with outstanding mechanical, adhesive and frictional properties benefit from their hierarchical composite structures, within which the reinforcing role of metal complexation in the polymer network phase was recently highlighted12. For example, it was reported that the Fe-catecholate (1,2-dihydroxybezene) complexes in mussel byssus cuticles provide effective crosslinking strategies between metal ions and catecholic amino acid dopa (3,4-dihydroxypheylalanine) in mussel foot protein 1 (mfp-1) chains13.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chitin plays a major role in biological structural materials with significant physical attributes, such as lobster shells [44], the mineralized dactyl club of the stomatopods [97,112], diatoms cell [20], glass sponges [52], copepod teeth's [115], spider fangs [116] and nacre [117]. Surprisingly, the industrial uses of chitinous materials have been largely based on its chemical characteristics (e.g., high nitrogen content) and unique biological properties, rather than on its ability to form structural composites with novel mechanical properties [117].…”
Section: Mechanical Stability Of Chitin-based Materialsmentioning
confidence: 99%